Analisis Penegakan Hukum Yang Tepat Bagi Pelaku Penyalahgunaan Narkotika Dalam Perspektif Hak Asasi Manusia - Kurniawan, Syahfrin; Joharsyah, Joharsyah; Sahbudi, Sahbudi (Universitas Medan Area, 2025)
The enforcement of narcotics laws in Indonesia continues to face significant challenges, particularly in distinguishing drug abusers as victims of addiction rather than conventional offenders. This study, titled “Human Rights-Based Legal Enforcement for Narcotics Abusers: A Study of the National Narcotics Agency (BNNK) Serdang Bedagai”, aims to examine the human rights protections afforded to narcotics abusers, assess appropriate sanctions under the Narcotics Law, and identify obstacles and potential solutions within the jurisdiction of BNNK Serdang Bedagai. Using normative and empirical juridical methods with statutory and conceptual approaches, data were collected through literature studies and interviews with relevant stakeholders, followed by qualitative descriptive analysis. The findings indicate that human rights protections for narcotics abusers have been guaranteed by the 1945 Constitution, Law No. 39 of 1999 on Human Rights, and Law No. 35 of 2009 on Narcotics, which mandate both medical and social rehabilitation for addicts. However, in practice, law enforcement officers often impose imprisonment without considering rehabilitation, thereby potentially violating rights to health and justice. The appropriate sanction for narcotics abusers is rehabilitation, as they are categorized as victims requiring recovery. Key obstacles include limited rehabilitation facilities, societal stigma, and inadequate understanding of human rights perspectives among officers. Strengthening institutional coordination, expanding rehabilitation infrastructure, and increasing public awareness are essential to ensuring humanistic and rights-based narcotics law enforcement.